2006
DOI: 10.2140/agt.2006.6.1623
|View full text |Cite
|
Sign up to set email alerts
|

TheC–polynomial of a knot

Abstract: In an earlier paper the first author defined a non-commutative A-polynomial for knots in 3-space, using the colored Jones function. The idea is that the colored Jones function of a knot satisfies a non-trivial linear q -difference equation. Said differently, the colored Jones function of a knot is annihilated by a non-zero ideal of the Weyl algebra which is generalted (after localization) by the non-commutative A-polynomial of a knot.In that paper, it was conjectured that this polynomial (which has to do with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…7 The algorithm which computes difference equations of minimal order for multi-sum expressions has been developed by S. Garoufalidis and X. Sun [67,72,73]. By the algorithm with a certicate, the quantum A-polynomials were obtained for the twist knots A(K p ;x,ŷ; q) in the range −14 ≤ p ≤ 15 [67].…”
Section: Quantum Super-a-polynomials For Twist Knotsmentioning
confidence: 99%
“…7 The algorithm which computes difference equations of minimal order for multi-sum expressions has been developed by S. Garoufalidis and X. Sun [67,72,73]. By the algorithm with a certicate, the quantum A-polynomials were obtained for the twist knots A(K p ;x,ŷ; q) in the range −14 ≤ p ≤ 15 [67].…”
Section: Quantum Super-a-polynomials For Twist Knotsmentioning
confidence: 99%
“…For computations of recursion relations of the cyclotomic function of twist knots, we refer the reader to [12].…”
Section: Recursion Relations For the Cyclotomic Function Of Twist Knotsmentioning
confidence: 99%
“…With our definition, we have c −1,n (q) = 1 and c 1,n (q) = (−1) n q n(n+3)/2 . In [GS06] it was shown that for each integer p, the sequence c p,n (q) satisfies a monic recurrence of order |p| with initial conditions c p,n (q) = 0 for n < 0 and c p,0 (q) = 1. In particular, for p = 2 we have: We employ the definition of J K p,p ′ ,n (q) given in (3) and (4) in terms of definite sums to compute a recurrence for the colored Jones polynomial of 7 4 = K 2,2 .…”
Section: The Colored Jones Polynomial Of Double Twist Knotsmentioning
confidence: 99%